2017
DOI: 10.4103/0259-1162.186861
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of butorphanol and fentanyl for the relief of postoperative shivering associated with spinal anesthesia

Abstract: Aim:The aim of this study was to compare fentanyl and butorphanol for the relief of postoperative shivering in spinal anesthesia.Materials and Methods:A total of 100 American Society of Anesthesiologists physical status Class I and II patients aged 19–60 years belonging to both sexes who were posted for elective surgical procedures under spinal anesthesia were divided into two groups (fentanyl and butorphanol) and monitored intraoperatively for the occurrence of shivering and time taken to control shivering af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…butorphanol can effectively treat shivering after spinal anesthesia, but there are few studies on general anesthesia and shivering prevention. [23][24][25] In this study, we found that butorphanol can effectively reduce the occurrence and intensity of postoperative shivering, which is similar to the results of previous studies. Sujeet 6 concluded that 2 mg of butorphanol administered intravenously before induction of anesthesia or performing the regional block reduced shivering after general anesthesia or intraspinal anesthesia.…”
supporting
confidence: 90%
“…butorphanol can effectively treat shivering after spinal anesthesia, but there are few studies on general anesthesia and shivering prevention. [23][24][25] In this study, we found that butorphanol can effectively reduce the occurrence and intensity of postoperative shivering, which is similar to the results of previous studies. Sujeet 6 concluded that 2 mg of butorphanol administered intravenously before induction of anesthesia or performing the regional block reduced shivering after general anesthesia or intraspinal anesthesia.…”
supporting
confidence: 90%
“…Butorphanol has the advantages of the strong analgesic effect, long analgesic time, light gastrointestinal side effects, less respiratory inhibition, and low drug dependence. At the same time, butorphanol could significantly prevent postoperative shivering and ease restlessness in patients under general anesthesia [ 37 ]. Generally, CRBD is resistant to traditional opioids, but butanediol-activated K receptors might ameliorate CRBD by inhibiting nociceptive stimulation of bladder neck spasm and urinary tract mucosa damage, and butorphanol did not increase the general rate of postoperative queasiness, dizziness, respiratory inhibition, low blood pressure, and hypertension [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, dexmedetomidine may require more time to achieve sufficient anxiolysis and induce sleep compared to propofol. It is crucial to note that dexmedetomidine is associated with common adverse effects like hypotension and bradycardia, which are significant factors to consider when selecting a sedative medication [42]. Despite the availability of traditional drugs like midazolam and ketamine for sedation during MRI, they exhibit lower sedation success rates, prolonged recovery times, and significant adverse events [3].…”
Section: Efficacy: Comparative Effectiveness In Achieving Adequate Se...mentioning
confidence: 99%